State sovereignty and alternative community in southern Africa: exploring the Zion Christian Church as the building block for deeper notions of regional community - Radebe, Zandisiwe (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2008)
Regional community in southern Africa has been limited to the region's states. As a result, deeper notions of community emanating from non-state actors, particularly transnational social movements, continue to be ignored. In an attempt to transcend state centrism, this thesis highlights alternative forms of regional community by exploring the Zion Christian Church (ZCC), one of southern Africa's biggest and fastest growing cross-border movements. The ZCC is a potential agent for developing regional community from the bottom-up, driving a people-oriented regional integration approach in southern Africa. The ZCC, with its extensive following among the region's poor, offers a compelling example of a grassroots and truly bottom-up approach to regional community. This thesis explores the possibility of the ZCC as a model of alternative community and identity centred on people's daily experiences and grounded in a shared history and solidarity. It seeks to highlight the significance of transnational movements like the ZCC to policy makers in the region and it argues that grassroots communities are marching ahead of SADC member states and politicians in the area of integration. There exists a transnational cooperation amongst followers of the ZCC and other grassroots communities across the region and this cooperation transcends the traditional notion of state sovereignty, thereby highlighting deeper notions of what it means to be a community at regional level.
Keywords: Zionist Christian Church; Southern African Development Community; Community development -- Africa, Southern; Regionalism -- Africa, Southern; Sovereignty -- Africa, Southern; Africa, Southern -- Economic integration